Epidemiologia da infecção pelo vírus da hepatite C em catadores de materiais recicláveis em Goiânia, Goiás - Marinho, Thaís Augusto (2012)
Hepatitis C represents an important public health problem. Although acute hepatitis C virus (HCV) infection is often asymptomatic, 50 to 85% of these cases progress to chronic disease, and can lead to liver cirrhosis and hepatocellular carcinoma. Accidents involving contaminated sharps occur in recyclable waste collectors as a result of contact with glass, ferrous sharp, needles and syringes, demonstrating, thus, the increased risk of these professionals in acquiring infections by the parenteral route, such as hepatitis C. There is currently very little data on HCV infection among recyclable waste collectors. This study aimed to investigate the epidemiological and molecular profile of the hepatitis C virus infection among recyclable waste collectors in Goiânia, Goiás. A total of 431individuals were interviewed for socio-demographic characteristics and risk factors for HCV infection. Blood samples were collected and sera were tested for the presence of antibodies to HCV (anti-HCV) using an enzyme-linked immunosorbent assay (ELISA) and immunoblot. All samples were submitted to HCV RNA detection by polymerase chain reaction (PCR) with primers complementary to the conserved area of the 5’ non-coding (NC) region of HCV. Positive HCV RNA samples were genotyped by direct sequencing analysis of the NS5B region of viral genome, followed by phylogenetic analysis. The HCV infection prevalence was 1.6% (95% CI: 0.6-3.6) in recyclable waste collectors in Goiânia-GO. In a multivariate analysis, history of sexually transmitted disease was independently associated with this infection, while the variables history of blood transfusion and number of sexual partners showed an association with a borderline P value (p = 0.05 and p = 0.07, respectively). Viral RNA was detected in five of the seven anti-HCV positive samples, and the genotype 1, subtypes 1a (n = 1), 1b (n = 2) and 1a/1b (n = 2) were identified in the study population. Although the HCV infection prevalence found among recyclable waste collectors in Goiânia-GO is similar to that observed in local blood donors (1.4%), this population is in risk to HCV by sexual and parenteral transmission.